The ballad of Lefty Brown - Moshé, Jared; Pullman, Bill; Fonda, Peter, 1940-; Spears, Michael, 1977- (Santa Monica, California : Lionsgate, 2018)
After a famed lawman and elected Montana senator is murdered, his sidekick sets out to get revenge for his friend's death.
Originally released as a motion picture in 2017.
Dolby digital 5.1, wide screen 1.85:1.
Bill Pullman, Peter Fonda, Michael Spears, Joseph Anderson, Dillinger Steele.
MPAA rating: R.
In English with optional English or Spanish subtitles.
Closed-captioned.
Keywords: Outlaws -- Drama; Revenge -- Drama; Frontier and pioneer life -- Drama; Montana -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Western films